Exploring the Link between ICT and Development in the Context of Developing Countries: A Literature Review. Issue 1 (5th December 2017) - Thapa, Devinder; Sæbø, Øystein
Abstract: The article contributes to the ongoing discussion on relating information and communication technology (ICT) to development (D). The quest to relate ICT to D is a topic of open deliberation and critical scrutiny in ICT4D research communities. To enhance the understanding in this regard, we conducted a literature review. The review examines 80 articles to identify various development theories and the role of technologies in the development process. While scanning the articles, Sen's capability approach (CA) emerged as a suitable framework with which to explore the link between ICT and D. To show the relevance of the link, we used the CA as a guiding framework, and reanalyzed ten empirical case studies focusing on projects in remote and rural areas. Furthermore, the article suggests six gaps in the current research, and, accordingly, six areas for future research.